Profiling dan pemetaan riset innovation ambidexterity melalui pendekatan bibliometrik - Rumangkit, Stefanus; Arief, Mts; Alamsjah, Firdaus; Elidjen (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
This study aims to provide a comprehensive picture of current conditions and future research potential in innovative ambidexterity research. To achieve this goal, this study uses a bibliometric approach, the data sources used are secondary data sources, where the data used is in the form of 81 research articles taken in the Scopus database. In addition, selected articles are published by well-known publishers, namely Elsevier, Inderscience Publishers, Springer, Emerald, Routledge, Cogent, and Sage Publications. The results of the co-occurrence analysis and thematic map outline various emerging research topics in its clusters. Dimanqa cluster 1 covers issues such as Construction Industry, Corporate Social Responsibility, Environmental Innovation, Finance, Functional Laterity, Hemispheric Dominance, Human Resources Management, Management Practice, Manufacturing, Microfoundation, Open Innovation, Performance, Social Capital, and Sustainability. Cluster 2 raised topics such as business development, competitiveness, digital transformation, information management, information processing, innovation performance, investment, marketing, organizational framework, performance assessment, regression analysis, social network, and sustainability development. Meanwhile, cluster 3 highlights The third cluster consists of empirical analysis, entrepreneurial orientation, exploitation, exploration, industrial performance, intellectual capital, pharmaceutical industry, strategic entrepreneuship, technological development. The fourth cluster consists of business performance, dynamic capabilities, enterprise resource management, industrial management, information analysis, knowledge management, knowledge transfer, least squares approxima, radical innovation. Meanwhile, the fifth cluster consists of connectedness, decision making, environmental dynamis, firm performance, knowledge management, technological innovation, top management team. The sixth cluster consists of absortive capacity, business process performance, exploitative innovation, exploration innovation, and Small Medium Enteprise. And, the seventh cluster consists of competitive intensity. Future research themes in the realm of innovation ambidexterity can be presented or connected with strategic entrepreneurship, exploitative innovation, digital transformation, and innovation performance.